1971
DOI: 10.1128/aem.21.1.84-89.1971
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Hemagglutination Test for Detection of Antibodies to Cytomegalovirus

Abstract: An indirect hemagglutination test has been adapted for use with cytomegalovirus. The test is highly sensitive and reproducible. Both immunoglobulin M and immunoglobulin G antibodies can be detected by this method. The hemagglutination reaction can be inhibited by small amounts of homologous antigen. This principle permits early identification of virus isolated from diagnostic specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 3 publications
(3 reference statements)
1
17
0
Order By: Relevance
“…It follows, therefore, that both procedures could be used with confidence for screening sera for these applications. It should be emphasized that the calculations of predictive value performed in this study should be applicable to general laboratory practice, since the prevalence of CMV antibody in our sample (i.e., 44.8%) closely approximates that reported for the general population (i.e., 40 to 70%) (2,3,6).…”
Section: Methodssupporting
confidence: 70%
“…It follows, therefore, that both procedures could be used with confidence for screening sera for these applications. It should be emphasized that the calculations of predictive value performed in this study should be applicable to general laboratory practice, since the prevalence of CMV antibody in our sample (i.e., 44.8%) closely approximates that reported for the general population (i.e., 40 to 70%) (2,3,6).…”
Section: Methodssupporting
confidence: 70%
“…All plasma specimens were stored at -20 C and later tested simultaneously in duplicate under code with the same CMV antigen preparation. The method of Bernstein and Stewart (1) with minor modifications (personal communication, John A. Stewart) was used for the preparation of antigen (AD 169 strain) and for the measurement of indirect hemagglutination (IHA) antibody. Complement-fixing (CF) antibody was measured by the Laboratory Branch microtiter CF technique (2).…”
Section: Methodsmentioning
confidence: 99%
“…Rubella Viruses Antibodies to CMV were measured using complement fixation (CF) and an indirect hemagglutination test (IHA). 22 Antibodies to varicella-zoster (VZ) were measured using CF and an immune adherence hemagglutination-" while those to rubella were measured by single-radial hemolysis and hemagglutination-Inhibition'" and those to herpes hominis (HH) by CF and IHA methods." RESULTS We found that many of the pregnant women showed reactivation of EBV as evidenced by excretion of virus in throat and by elevated IgG anti-VCA and anti-EA.…”
Section: Antibodies To Cytomegalovirus Varicella-zoster Andmentioning
confidence: 99%